Permanent deformation response of demolition wastes stabilised with bitumen emulsion as pavement base/subbase. (March 2023) - Yaghoubi, Ehsan; Ghorbani, Behnam; Saberian, Mohammad; van Staden, Rudi; Guerrieri, Maurice; Fragomeni, Sam
Highlights: A slow-set anionic bitumen emulsion was used for road base/subbase application. A series of multi-stage RLT tests at five distinct stress combinations were conducted. Effect of in-service moisture on permanent deformation of aggregates was studied. Addition of emulsion to the aggregates led to an increase in resilient strains. The majority of the stabilized RCA and CB samples exhibited plastic creep responses. Abstract: The stabilisation of the granular base course using binders has been adopted for many years; however, the use of bitumen emulsions has been emerging in recent times. Nevertheless, there is limited knowledge on the deformation behaviour of bitumen emulsion-stabilised recycled demolition wastes, particularly in pavement base and subbase applications. In this study, the effect of bitumen emulsion on the permanent deformation behaviour of two types of recycled demolition wastes, recycled concrete aggregate (RCA) and crushed brick (CB) is evaluated. The aggregate samples were blended with an anionic slow-set bitumen emulsion at different contents of 0, 1, 2, and 3 % by dry weight of aggregates. Compacted specimens were partially dried to achieve target values of 70 and 90 % of their optimum moisture contents to investigate the effect of in-service moisture content. Specimens were next subjected to repeated loading triaxial tests that comprised of multiple stages at varying stress levels to simulate moving loads of vehicles. The shakedown theory was adopted to characterise the blends based on their permanent deformation responses. Most of the proposed blends exhibited a Range B behaviour, i.e., plastic creep responses. Also, CB samples generally experienced higher permanent strain accumulations and hence, inferior permanent deformation responses compared to RCA. The inclusion of bitumen emulsion to the aggregates generally caused a decrease in resilient strains, showing that emulsion-stabilised RCA and CB could provide increased resistance under repeated traffic loading. It was also concluded that higher moisture contents led to higher permanent strains and permanent strain rates.